Conflict and Adaptation Between Christian Religious and Secular Roles: An Empirical Study of QN Church in Bozhou City - LIANG, Xiaowei; WU, Bijun (Journal of Research for Christianity in China (JRCC), 2025)
As a religious group, Christians bear the different roles of religion and secular in social life. On the one hand, they are Christians as "children of God", on the other hand, they are members of society and have different Family and professional roles, etc. There may be some conflicts between these two distinct characters, may causing some confusion for Christians’ social life. Through in-depth interviews with 8 Christians in the QN church in Bozhou City, this paper deeply explores the manifestations and causes of the conflicts, as well as the ways in which Christians cope with role conflicts and ways to alleviate role conflicts.